The Labor Market Effects of Venezuelan Migration in Ecuador - Sergio Olivieri; Francesc Ortega; Ana Rivadeneira; Eliana Carranza (Institute of Labor Economics (IZA), 2020)
As of 2019, more than 1.2 million Venezuelans have passed through Ecuador and over 400,000 settled in, which amounts to almost 3% of Ecuador's population. This paper analyzes the location choices of Venezuelan migrants within Ecuador and the labor market consequences of these choices, using data from Ecuador's labor force survey (ENEMDU) and mobile phone records on the geographic distribution of Venezuelan migrants. Around half of these migrants live in 4 cantons (out of 221). Their location is primarily driven by local economic conditions, rather than point of entry. Overall, regions with the largest inflows of Venezuelans have not seen any effects on labor market participation or employment, compared to regions with fewer inflows. However, our difference-in-difference estimates clearly indicate that young, low-educated Ecuadorian workers in high-inflow regions have been adversely affected. Specifically, we estimate that these workers have experienced reductions in employment quality, a 5 percentage-point increase in the rate of informality, and a 13 percentage-point reduction in earnings, relative to workers with similar characteristics living in areas with very low or non-existing inflows of Venezuelans.
Keywords: O15; J61; D31; 330; migration Venezuela; labor market